Pengaruh Intensitas Modal, Kepemilikan Manajerial, Profitabilitas terhadap Manajemen Laba dengan Ukuran Perusahaan sebagai Pemoderasi - Dwi Renaldy Putra; David Pangaribuan; Panata Bangar Hasioan Sianipar (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
Accurate and transparent financial reporting is crucial in building investor trust and ensuring the confidence of other stakeholders. However, earnings management remains a key concern in accounting and finance as it affects the quality of financial information and economic decision-making. This study aims to analyze the influence of Capital Intensity, Managerial Ownership, and Profitability on Earnings Management, with Firm Size as a moderating variable. Using a quantitative approach with the deducto hypothetico verifikatif method, this study empirically tests hypotheses through inferential statistical analysis. The results show that Capital Intensity and Managerial Ownership have a negative effect on Earnings Management, while Profitability has a positive effect. Furthermore, Firm Size does not moderate the effect of Capital Intensity on Earnings Management but weakens the influence of Managerial Ownership and strengthens the effect of Profitability on Earnings Management. This study is expected to provide insights for investors, managers, and regulators in understanding the factors influencing earnings management practices and their implications for financial reporting quality.